MEMORY TRANSMISSION IN DORA BRUDER NOVEL: A POST-MEMORY ANALYSIS - Hanif, Fauzan; Udasmoro, Wening; Tri Astuti, Wulan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
Traumatic events such as the Holocaust transcend through generations. Hirsch strengthens this argument by saying that post-memory is a study of the structure of intergenerational and trans-generational memory transmission in the form of traumatic knowledge and experiences. This study raises the meaning of memory transmission in the Dora Bruder novel by Patrick Modiano. The method used in this article is the content analysis of the story. The data are collected form of sentences that describe the meaningful forms of memory transmission. There are three interpretations from the results of memory transmission. They are the narrator’s interpretation of a location as signifiers of the incommensurability of return, the narrator’s interpretation as an agent and actor of allo-identification, and the emergence of a desire to reject the act of forgetting. Analysis using post-memory illustrates that the generation of heirs to the traumatic memories inherits various challenged and debated questions, intending to expose and retell that story to the public.